Pedagogi Kritis: Pemikiran Henry Giroux Tentang Pendidikan dan Relevansinya untuk Indonesia - Reza Alexander Antonius Wattimena (Jurnal Filsafat "WISDOM", 2018)
This paper is a critique toward traditional pedagogy in education through a critical pedagogy perspective as formulated by Henry Giroux. Critical pedagogy is an attempt to question and to uncover the existing power relations in society which create various forms of subordination and social injustice. Critical pedagogy offers extended perspective as well as moral sensibility that encourage engagement in efforts of bringing social changes to produce freedom and justice in the society. According to Giroux, critical pedagogy provides various theoretical tools to examine neoliberalist mindset that spreads in various dimensions of human life. This writing furtjer seeks possibility to apply the concept of critical pedagogy in Indonesian context.